Did US regions with manufacturing design generate more production jobs in the 2000s? New evidence on innovation and regional development. (October 2017) - Doussard, Marc; Schrock, Greg; Lester, T William
US manufacturing policies increasingly steer resources toward the act of innovation. Emerging case-study evidence suggests that this innovation leads to manufacturing job growth. However, the case-study evidence from which this claim is assembled is incomplete and selective. Using regional-level industry-occupation data for US manufacturing sectors, we test the contribution of manufacturing innovation activities to production employment growth within US regions, for the 2000–2006 and 2006–2010 periods. While production employment continued to disperse from sites of historical manufacturing concentration over both time periods, innovation activities provided some advantages. From 2000 to 2006, regions with higher innovation concentrations in high-tech and medium–low technology industries, experienced slower rates of production employment decline. From 2006 to 2010, a period spanning the Great Recession, innovation activities were associated with reduced production job losses for industries of all technology levels. These results indicate that innovation has benefits beyond high-technology industries, but that those benefits are limited and selective.